2010
DOI: 10.1074/jbc.m109.064972
|View full text |Cite
|
Sign up to set email alerts
|

ERK Nuclear Translocation Is Dimerization-independent but Controlled by the Rate of Phosphorylation

Abstract: Upon activation, ERKs translocate from the cytoplasm to the nucleus. This process is required for the induction of many cellular responses, yet the molecular mechanisms that regulate ERK nuclear translocation are not fully understood. We have used a mouse embryo fibroblast ERK1-knock-out cell line expressing green fluorescent protein (GFP)-tagged ERK1 to probe the spatiotemporal regulation of ERK1. Real time fluorescence microscopy and fluorescence correlation spectroscopy revealed that ERK1 nuclear accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 49 publications
(50 reference statements)
6
79
0
Order By: Relevance
“…EGFR-induced kinase pathways are known to modulate steroid receptor-mediated transcriptional signaling by altering both receptor and co-regulator activities (10,11,44,45,49,50,59,60). Thus, indirect activation of the EGFR by DHT similarly leads to "outside-inside" cross-talk whereby rapid activation of extra-nuclear kinases enhances intra-nuclear transcriptional signaling.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR-induced kinase pathways are known to modulate steroid receptor-mediated transcriptional signaling by altering both receptor and co-regulator activities (10,11,44,45,49,50,59,60). Thus, indirect activation of the EGFR by DHT similarly leads to "outside-inside" cross-talk whereby rapid activation of extra-nuclear kinases enhances intra-nuclear transcriptional signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The ERK2 NLS is also problematic due to structural reasons: the proposed site is rigidly folded and does not appear to be available for intramolecular autophosphorylation. ERK1/2 more likely translocates into the nucleus following activation loop phosphorylation-dependent formation of its FxFP pocket and subsequent interactions with FxFG motif-containing nucleoporin proteins of the nuclear pore complex, a mechanism not possible for JNKs (139)(140)(141). Regardless, nuclear translocation of both active and inactive MAPKs may also be mediated by several ␤-importins.…”
Section: Jnk Nucleo-cytoplasmic Traffickingmentioning
confidence: 99%
“…Regarding the role of MAPKs in NF-κB activation, earlier work showed that p38 pathway can influence NF-κB activation, at least partly, through the physical association with MAPK6 (Craig et al, 2000;Yoo et al, 2012). In addition, pERK1/2 was reported to have the ability to translocate into the nucleus, where it phosphorylates various substrates, such as transcriptional factors, thereby transmitting the signals received by cell surface receptors to the nucleus (Lidke et al, 2010). Hence, it is conceivable that H2O2 has a potential role in promoting the NF-κB pathway through the activation of ERK and p38 MAPK.…”
Section: Figurementioning
confidence: 99%